RED FLAG IN THE PEARL OF THE ORIENT? - Liwanag, Lois Mauri Anne L.; Mendoza, Tiffany Ritz F.; Enriquez, Sophia Marie V.; Joven, Vianca Jamyla A.; Liwanag, Leslie Anne L.; Chua, Michael Charleston "Xiao" B. (Kritika Kultura, 2025)
This paper attempts to deduce how certain articles in La Solidaridad that specifically discussed China present a general image of the said Celestial Empire. Its significance lies in the fact that it can provide further knowledge of how Filipino intellectuals of that time perceive the Philippines in relation to its neighbors in Asia as well as the dynamics of the region's political situation. This article is also important due to its potential to provide a Filipino perception of China before it was altered by the Philippine-Chinese territorial conflict that emerged during the latter part of twentieth century. This paper has five substantive sections on how the articles talked about the following: the First Sino-Japanese War, Chinese in the Philippines, Chinese in mainland China, Chinese territorial disputes, and Chinese in some other parts of the world. This study shows that the image of China in La Solidaridad developed from a combination of perspectives influenced by the anxieties of the Spanish Empire, the detachment of the Austro-Hungarian Empire, and the reformist aspirations of Filipino intellectuals seeking assimilation. The paper gives further historical contexts to the current challenges in Filipino and Chinese diplomacy in the face of the West Philippine Sea issue.